A Systems Engineering Perspective on the Revised Defense Acquisition System. Issue 6 (8th January 2016) - Cilli, Matthew; Parnell, Gregory S.; Cloutier, Robert; Zigh, Teresa
ABSTRACT: The U.S. Department of Defense (DoD) has recently revised the defense acquisition system to address suspected root causes hindering higher success rates. This article applies two systems thinking methodologies in a uniquely integrated fashion to provide an in‐depth review and compelling interpretation of the revised defense acquisition system as put forth in January 7, 2015 DoDI 5000.02. Changes from the previous defense acquisition system are significant and may be cause for some cautious optimism in the United States. This article describes how the architects of the revised defense acquisition system have increased emphasis on systems engineering activities applied early in the lifecycle so that meaningful trade‐offs between capability requirements and lifecycle costs can be explored as requirements are being written to ensure realistic program baselines are established such that associated lifecycle costs will likely fit within future budgets. Expressed as emerging systems engineering research questions, this article identifies several gaps that are likely to emerge as the defense acquisition community attempts to execute the new acquisition system.